THE ESTABLISHMENT PROCESS OF ISLAMIC THEOLOGY IN GERMAN UNIVERSITIES - Ibrahim Kocyigit (Journal of Islamic, Social, Economics and Development, 2019)
After the recommendations on the Advancement of Theologies and Sciences concerned with Religions at German universities in 2010 the new subject, â€žIslamic Theologyâ€ is faced with different expectations by various interest groups from the very start. For politicians and media the mission of â€žIslamic Theologyâ€ is to train religious scholars, Imams, religious teachers and social workers. Together with this challenge, the new subject should give answers to questions relating to integration: Moreover, â€žIslamic Studiesâ€, a subject with a longer tradition feels itself in competition with â€žIslamic Theologyâ€œ. The Islamic organizations try to be a part of the decision making process. The expert representatives of the subject try to meet the different and sometimes even opposed expectations.